A EVALUATION OF THE LEVEL OF PATIENT SATISFACTION WITH PHARMACEUTICAL SERVICES IN THE INSTALLATION OF OUTPATIENT PHARMACY ISLAMIC HOSPITAL PURWOKERTO - Dewi, Iva Rinia; Kholid, Rofik; Solikhah, Putu Maratus; Cahyani, Arinda Nur (Jurusan Kesehatan Masyarakat dan Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2025)
Hospital is a comprehensive health service facility that includes inpatient, outpatient, and emergency services. Patient satisfaction is the perception of the patient that his expectations have been met, the purpose of the study to determine the number of patient satisfaction in Outpatient Pharmacy installation Islamic Hospital Purwokerto based on the dimensions of real evidence (Tangibles), Responsiveness (Responsiveness), assurance (Assurance), empathy (empathy) and reliability (Reliability). This type of research is descriptive research with cross sectional approach. The sampling method used in this study is accidental sampling. The results of this study showed female respondents with a percentage of 65.6%. with an adult age category with a percentage of 49.5%. History of high school education with a percentage of 43%, self-employed jobs with a percentage of 29.0%. The results of the level of satisfaction based on 5 dimensions of concrete evidence 74.19%, 75.91% responsiveness, assurance 75.91%, empathy 73.76%, reliability 75.27%. Further research suggestions for researchers are expected to develop this study to determine the relationship characteristics of respondents with the level of patient satisfaction.